Liposomes-based co-delivery of pheophorbide a and gold nanoparticles for thermo-photodynamic therapy purpose on lung cancer spheroids - Kave Moloudi; Heidi Abrahamse; Blassan P. George (Results in Chemistry)
Co-delivery of drugs in nanotechnology is a novel area of cancer therapy. In this study, we designed and synthesized a new nanocomplex (Lipo@AuNPs@PPBa) as photosensitizer (PS) from gold nanoparticles (AuNPs) and pheophorbide a (PPBa) for photodynamic therapy (PDT) and photothermal therapy (PTT) application in A549 lung cancer spheroids. The thin-film hydration method used for synthesis of Lipo@AuNPs@PPBa. UV–vis spectroscopy, TEM, SEM, DLS and FTIR were performed to characterise the NPs. ATP, LDH, MTT, the live-dead assay, and flow cytometry were used to assess the therapeutic effect of NPs on A549 spheroids with and without a 660 nm laser. TEM data showed the size of Lipo@AuNPs@PPBa was 87.8 nm and EDS confirmed that AuNPs and PPBa were loaded onto liposomes. Furthermore, the data illustarted that low concentrations of AuNPs (<50 μg/mL) and PPBa (<6 μM) did not show significant effect on A549 spheroids but 60 μg/mL of Lipo@AuNPs@PPBa reduced cell viability to 52.25 % in single treatment and 33.2 % in combination with 660 nm laser. Also, Lipo@AuNPs@PPBa complex presented PTT on A549 spheroids in vitro and increased temperature around 7–8 °C in cell culture media. Moreover, Lipo@AuNPs@PPBa caused cell cycle arrest at G2/M, apoptotic cell death via activite of pro-apoptotic proteins including BAX and caspase-9 (CASP9) in A549 lung cancer spheroids.In conclusion, Lipo@AuNPs@PPBa showed potential to be a PS in PDT of lung cancer. Furthermore, AuNPs demonstrated to enhance the efficacy of synergistic effect on PPBa mediated PDT and PTT.